2017
DOI: 10.1021/acs.jnatprod.6b00771
|View full text |Cite
|
Sign up to set email alerts
|

Suberin Fatty Acids from Outer Birch Bark: Isolation and Physical Material Characterization

Abstract: The isolation and physical material properties of suberin fatty acids (SFAs) were investigated with special reference to their potential applications as novel pharmaceutical excipients. SFAs were isolated from outer birch bark (OBB) with a new extractive hydrolysis method. The present simplified isolation process resulted in a moderate batch yield and chemical purity of SFAs, but further development is needed for establishing batch-to-batch variation. Cryogenic milling was the method of choice for the particle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…Kitin et al (2020) also reported the fluorescence of lignin and suberin in plant cells under CLSM. Heinämäki et al (2017) confirmed the melting behavior of suberin monomers. Therefore, the fluorescence of cell wall was brighter and SMs have a uniform distribution after heat treatment.…”
Section: Sms Distribution In the Specimenssupporting
confidence: 70%
“…Kitin et al (2020) also reported the fluorescence of lignin and suberin in plant cells under CLSM. Heinämäki et al (2017) confirmed the melting behavior of suberin monomers. Therefore, the fluorescence of cell wall was brighter and SMs have a uniform distribution after heat treatment.…”
Section: Sms Distribution In the Specimenssupporting
confidence: 70%
“…The high proportions of lignin, cellulose, and hemicellulose ( Figure 2) suggest a high calorific value of the material as well as low ash content. In addition, in the case of birch bark, the extractive compounds ( Figure 2) may include suberin and betulin, which are the main components giving 1.5 times higher heating value in comparison with wood components (Ferreira et al, 2013;Heinamaki et al, 2017). Several studies have shown that there was a highly significant linear correlation between the higher heating value of the extractive-free wood and lignin content (Demirbaş, 2001;White, 1987) and another one showed that high ash content in parts of a plant makes it less desirable as fuel (Demirbas, 2002).…”
Section: Characterization Of Extractsmentioning
confidence: 99%
“…Birch outer bark is rich in valuable biochemicals like the naturally occurring biopolyester suberin and the triterpenoids betulinol and lupeol [12,13,14,15,16]. The content of betulinol and lupeol in outer bark varies between 30%–35% and the content of suberin can be up to 40%–50% [13,17].…”
Section: Introductionmentioning
confidence: 99%